2021
DOI: 10.1111/hae.14031
|View full text |Cite
|
Sign up to set email alerts
|

The effects of manual therapy on musculoskeletal system, functional level, joint health and kinesiophobia in young adults with severe haemophilia: A randomized pilot study

Abstract: Introduction The effects of manual therapy (MT) on joint health and functional level in haemophilic arthropathy (HA) have relatively under‐explored. Aim To investigate the effects of MT in HA of lower limb joints on musculoskeletal system, functional level, Functional Independence Score in Hemophilia (FISH), Hemophilia Joint Health Score (HJHS) and kinesiophobia. Methods Seventeen patients were randomized to the control group (CG = 9) and manual therapy group (MTG = 8). The number of haemarthrosis (NoH) was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…In that study, one group received a home-based programme consisting of strengthening and stretching exercises, while the other group received manual therapy additionally. Comparable improvements were demonstrated with FISH scores in both groups 39. In our study, post-treatment FISH scores showed improvement ver-sus baseline in both SG and CTG.…”
supporting
confidence: 55%
“…In that study, one group received a home-based programme consisting of strengthening and stretching exercises, while the other group received manual therapy additionally. Comparable improvements were demonstrated with FISH scores in both groups 39. In our study, post-treatment FISH scores showed improvement ver-sus baseline in both SG and CTG.…”
supporting
confidence: 55%
“…Fifty‐two articles 1,15,17–66 dealt with rehabilitation and preventive physiotherapy. Most of them aimed to map the options for the management of PWH or demonstrate the role of physiotherapy, not only in the presence of clinical problems but also for preventive purposes and to allow a healthy growth.…”
Section: Resultsmentioning
confidence: 99%
“…The patient was placed in a supine position and with his knees slightly flexed, and his foot off the stretcher. The axis of the goniometer was placed on the lateral side of the lateral malleolus, the fixed arm aligned with the fibula and the mobile arm parallel to the fifth metatarsal 31 . Goniometric assessment of ankle range of motion has shown high interobserver reliability (ICC: .85–.96) 33 .…”
Section: Methodsmentioning
confidence: 99%
“…Muscle strength was measured with a pressure dynamometer (Lafayette Manual Muscle Tester 01165) 30 . The patient was placed in a supine position with his foot at 90° dorsal flexion 31,32 . The patient was asked to conduct two 5‐s maximum isometric contractions, with a 30‐s break in between, against the dynamometer held by the evaluator 31,32 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation